Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

Regional climate downscaling simulations for China since the Last Glacial Maximum - Naixin Cao; Liang Ning; Jian Liu; Zhengyu Liu; Mi Yan; Weiyi Sun; Meiling Jiang; Xueyuan Kuang; Huayu Lu; Kefan Chen; Yanmin Qin; Qin Wen; et al. (Science China Earth Sciences, 2026)

Assessment of Spirulina Residue Meal as a Substitute for Fish Meal in Juvenile Rainbow Trout (Oncorhynchus mykiss) Diets: Impact on Growth, Antioxidative Capacity, Carcass Composition and Hepatointestinal Health - Ning Fu; Yuyu Wang; Shengwen Niu; Mengxin Xing; Meiling An; Lu Zhao; Gefeng Xu; Hairui Yu; Jiubo Cui (Fishes, 2026)
A 7-week study was conducted to investigate the effects of replacing fish meal (FM) with Spirulina residue meal (SPRM) on the growth, feed utilization, carcass composition, antioxidant ability, liver and intestinal histology of juvenile rainbow trout (Oncorhynchus mykiss) (initial body weight 5.36 ± 0.04 g). Four isonitrogenous (42%) and isolipidic (16%) diets were formulated to replace FM protein with SPRM at 0 (SPRM0), 10% (SPRM10), 20% (SPRM20) and 30% (SPRM30), respectively. Results showed that growth, feed utilization, carcass amino acid profile, serum biochemical indices, antioxidant ability, intestinal and liver histology were not significantly affected by dietary SPRM levels. Whole-body lipid content decreased as dietary SPRM replacement levels increased, and fish fed diet SPRM30 had lower lipid content than that fish fed diet SPRM0 (p 0.05). The muscle C22:6n-3 (DHA) content decreased, but C18:3n-6 and n-6/n-3 polyunsaturated fatty acid (PUFA) ratio increased with increasing SPRM levels, and fish fed diet SPRM30 had significantly lower DHA content and higher n-6/n-3 ratio than the group fed SPRM0 (p 0.05), but higher than the SPRM10 and SPRM20 groups (p

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

Research on high-resolution PM2.5 concentration estimation methods based on transfer learning - Meiling Xing; Bo Li; Wenhao Zhang; Guohong Li; Xiufeng Yang; Qiyue Liu; Qichao Zhao (Advances in Space Research, 2026)

Spatial accessibility to public electric vehicle charging infrastructure and multi-mechanism process of regional inequity in Greater Bay Area, China - Xing Gao; Huizi Wang; Ying Zhang; Keyu Zhai; Meiling Wu (Journal of Transport Geography, 2025)

Solar-driven superhydrophobic modified polyurethane sponge for rapid in-situ recovery of oil and microplastics in marine oil spill co-contamination - Chuanliang Zhao; Sidan Peng; Bo Wu; Le Kang; Lanlan Liang; Meiling Liu; Liwei Yang; Wendong Wang; Xing Xu (Journal of Hazardous Materials, 2025)

Changes in soil quality and crop productivity along rice cultivation chronosequences in saline-alkali soils - Bangyan Zhang; Jinmin Wu; Xiaolong Bai; Lei Li; Meiling Lin; Xing Xu; Fengju Zhang; Bin Wang (Journal of Environmental Management, 2025)

Ultrastable Ti@Ir core-shell catalyst with low iridium loading for water electrolysis at industrial-level current density - Jiahao Yang; Zhaoping Shi; Yibo Wang; Hongxiang Wu; Jing Ni; Pengbo Wang; Meiling Xiao; Changpeng Liu; Wei Xing (Chemical Engineering Journal, 2025)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

The immune function of heme oxygenase-1 (HO-1) from Nile tilapia (Oreochromis niloticus) in response to bacterial infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Molecular characteristics and functional analysis of non-specific cytotoxic cell receptor (NCCRP1) in golden pompano (Trachinotus ovatus) - Meiling Huang; Zhiqiang Zhang; Xing Li; Jiamin Feng; Yongxiong Huang; Amoah Kwaku; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Apolipoprotein Eb (On-ApoEb) protects Oreochromis niloticus against Streptococcus agalactiae infection - Jiamin Feng; Yongxiong Huang; Meiling Huang; Xing Li; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Interleukin-8 involved in Nile Tilapia (Oreochromis niloticus) against bacterial infection - Xing Li; Baijian Jiang; Zhiqiang Zhang; Meiling Huang; Jiamin Feng; Yongxiong Huang; Kwaku Amoah; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Structure regulation of two-dimensional composites facilitates solar/electric desalination - Xiaoran Cheng; Chenyang Xing; Weifeng Liu; Meiling Wang; Xuguang Liu; Jiadong Zhou (Chemical Engineering Journal, 2023)

Involvement of CD27 in innate and adaptive immunities of Nile tilapia (Oreochromis niloticus) - Baijian Jiang; Qi Li; Zhiqiang Zhang; Yongxiong Huang; Yiqin Wu; Xing Li; Meiling Huang; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2023)

Atomically dispersed metal catalysts towards nitrogen reduction for Ammonia: From homogeneous to heterogeneous - Di Yang; Jinsheng Li; Meiling Xiao; Changpeng Liu; Wei Xing; Jianbing Zhu (Chemical Engineering Journal, 2023)

Self-intercepting interference of hydrogen-bond induced flexible hybrid film to facilitate lithium extraction - Meiling Wang; Tianyuan Zhang; Zhixiang Meng; Chongji Wang; Weikang Dong; Jijian Liu; Su Yang; Xudong Hou; Xiaoran Cheng; Weifeng Liu; Chenyang Xing; Xuguang Liu; et al. (Chemical Engineering Journal, 2023)

Research progress on antidiabetic activity of apigenin derivatives - Jingyi Jiang; Ting Tang; Yaling Peng; Meiling Liu; Qianwen Liu; Pengbing Mi; Zehua Yang; Hongfei Chen; Xing Zheng (Medicinal Chemistry Research, 2022)

Two new monoterpene glucosides from Xanthium strumarium subsp. sibiricum with their anti-inflammatory activity - Hai Jiang; Xudong Xing; Meiling Yan; Xinyue Guo; Lin Yang; Liu Yang (Natural Product Research, 2019)